KONSEP MENGAJAR PERSPEKTIF AL-QUR’AN - asad asad (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2017)
Teaching in Al-quran uses the word ‘allamawas forty-one times in two sighat (pattern or scales) fi'il madhi and mudhari'. God taught Adam the names of the whole thing, that gave him the potential knowledge of the names or words used to designate objects, or teach them to recognize the functions of things, this verse informs that man is given the potential of God to know the name or function and the characteristics of objects, such as fire functions, wind functions, and so on. He was also awarded the potential for language. The language teaching system to humans (young children) does not begin by teaching verbs, but teach them first names. It's Dad, it's Mom, it's an eye, it's a pen, and so on.